Vozes sociais e dimensão ética da lingüística aplicada: a construção discursiva da área nos CBLAs - Archanjo, Renata (2008)
This research deals with Applied Linguistics and its structure as a scientific field, in compliance with knowledge produced within the range of the Brazilian Congresses of Applied Linguistics (CBLA). The purpose of this research is to understand the meanings disclosed by the voices that make up the scientific discourse on this field, pointing toward its course of development, the ethical position that is peculiar to it and how this position is represented in its scientific practice. The scientific discourse typical of the production of knowledge of Applied Linguistics is now construed as leading to practices that define the production of this field of learning whose object is to study man and man s relationship to language. Theoretical groundwork is anchored on the work the Social Sciences have developed on the paradigmatic crises of science and the social changes resulting from modern and post-modern times, on Applied Linguistics researches on the identity of the field of study, its courses and ethics, and on the bakhtinian theory that supports a view of language as a social practice built under the aegis of the subject s ethics and responsibility. The corpus of this work comprises qualitative and quantitative data made into articles presented at the CBLA. The research methodology conforms to the interpretive paradigm and has the concept of social voices as its category of analysis. Results point towards the progress of Applied Linguistics that, from its role as a mediator discipline between linguistic theory and practical applications, is assuming a position in a field of study of its own, independent, with transdisciplinary characteristics, pursuing through its quests and redefinitions to get closer to the dimension of life and assuming the ethical position of taking on responsibility for its doings and sayings